Use of Unmalted and Malted Buckwheat in Brewing - Marius Eduard Ciocan; Rozália Veronika Salamon; Ágota Ambrus; Georgiana Gabriela Codină; Ancuța Chetrariu; Adriana Dabija (Applied Sciences, 2023)
With the goal of introducing specialty beers with full flavor and effective processing, craft and functional beer have revived old assortments and established new assortments in countries throughout the world. These unique selections are produced utilizing various ingredient combinations or changes to the brewing process. Given the rise in celiac disease sufferers in recent years, research investigations on the use of buckwheat in brewing, particularly gluten-free beer, have intensified. In this study, malted and unmalted buckwheat were proposed for use in brewing, and the results were contrasted with those of beer made entirely of malted barley. Commercial enzymes were added to the technical mashing process in order to optimize it and increase output yield. It was simple to incorporate buckwheat in the technological process to produce a final product that, in many respects, resembled conventional beer, making buckwheat suitable for regular beer drinkers. In terms of original extract, apparent extract, alcohol content, and energy value, the beer obtained from 100% barley malt differs from the final beer, but only minor variations were found in color, pH, and bitterness value. Ethyl alcohol, a particularly significant distinguishing characteristic, was impacted by the use of buckwheat malt and unmalted buckwheat. The beer made from buckwheat was acceptable from a sensory perspective in terms of flavor, aroma, texture, bitterness, etc. The results demonstrate that the researched raw materials can be successfully used in the production of beer, both in malted and unmalted forms. For the latter option, it is recommended to use enzyme preparations to speed up the mashing and filtration of the wort.